Get reliable answers to your questions at Westonci.ca, where our knowledgeable community is always ready to help. Discover comprehensive answers to your questions from knowledgeable professionals on our user-friendly platform. Our platform offers a seamless experience for finding reliable answers from a network of knowledgeable professionals.
Sagot :
Let's simplify the given expression step-by-step:
The expression is:
[tex]\[ \left(\frac{\left(2^{-3}\right)\left(x^{-3}\right)\left(y^2\right)}{\left(4^{-2}\right)\left(x^4\right)\left(y^6\right)}\right)^2 \][/tex]
First, let's simplify the fraction inside the parentheses.
### Numerator:
[tex]\[ 2^{-3} \cdot x^{-3} \cdot y^2 \][/tex]
### Denominator:
[tex]\[ 4^{-2} \cdot x^4 \cdot y^6 \][/tex]
#### Simplify [tex]\( 4^{-2} \)[/tex]:
Note that [tex]\( 4 = 2^2 \)[/tex], so:
[tex]\[ 4^{-2} = (2^2)^{-2} = 2^{-4} \][/tex]
Therefore, the denominator becomes:
[tex]\[ 2^{-4} \cdot x^4 \cdot y^6 \][/tex]
Now we rewrite the entire fraction:
[tex]\[ \frac{2^{-3} \cdot x^{-3} \cdot y^2}{2^{-4} \cdot x^4 \cdot y^6} \][/tex]
### Simplify the fraction by dividing the corresponding bases:
#### For the base 2:
[tex]\[ \frac{2^{-3}}{2^{-4}} = 2^{-3 - (-4)} = 2^{-3 + 4} = 2^1 = 2 \][/tex]
#### For the base x:
[tex]\[ \frac{x^{-3}}{x^4} = x^{-3 - 4} = x^{-7} \][/tex]
#### For the base y:
[tex]\[ \frac{y^2}{y^6} = y^{2 - 6} = y^{-4} \][/tex]
So, the fraction simplifies to:
[tex]\[ 2 \cdot x^{-7} \cdot y^{-4} \][/tex]
Now, let's square the entire simplified expression:
[tex]\[ \left(2 \cdot x^{-7} \cdot y^{-4}\right)^2 \][/tex]
### Squaring each part separately:
#### For the coefficient 2:
[tex]\[ (2)^2 = 4 \][/tex]
#### For the base x:
[tex]\[ (x^{-7})^2 = x^{-7 \cdot 2} = x^{-14} \][/tex]
#### For the base y:
[tex]\[ (y^{-4})^2 = y^{-4 \cdot 2} = y^{-8} \][/tex]
Combining these results, we get:
[tex]\[ 4 \cdot x^{-14} \cdot y^{-8} = \frac{4}{x^{14} \cdot y^8} \][/tex]
Thus, the simplified form of the given expression is:
[tex]\[ \boxed{\frac{4}{x^{14} y^8}} \][/tex]
The expression is:
[tex]\[ \left(\frac{\left(2^{-3}\right)\left(x^{-3}\right)\left(y^2\right)}{\left(4^{-2}\right)\left(x^4\right)\left(y^6\right)}\right)^2 \][/tex]
First, let's simplify the fraction inside the parentheses.
### Numerator:
[tex]\[ 2^{-3} \cdot x^{-3} \cdot y^2 \][/tex]
### Denominator:
[tex]\[ 4^{-2} \cdot x^4 \cdot y^6 \][/tex]
#### Simplify [tex]\( 4^{-2} \)[/tex]:
Note that [tex]\( 4 = 2^2 \)[/tex], so:
[tex]\[ 4^{-2} = (2^2)^{-2} = 2^{-4} \][/tex]
Therefore, the denominator becomes:
[tex]\[ 2^{-4} \cdot x^4 \cdot y^6 \][/tex]
Now we rewrite the entire fraction:
[tex]\[ \frac{2^{-3} \cdot x^{-3} \cdot y^2}{2^{-4} \cdot x^4 \cdot y^6} \][/tex]
### Simplify the fraction by dividing the corresponding bases:
#### For the base 2:
[tex]\[ \frac{2^{-3}}{2^{-4}} = 2^{-3 - (-4)} = 2^{-3 + 4} = 2^1 = 2 \][/tex]
#### For the base x:
[tex]\[ \frac{x^{-3}}{x^4} = x^{-3 - 4} = x^{-7} \][/tex]
#### For the base y:
[tex]\[ \frac{y^2}{y^6} = y^{2 - 6} = y^{-4} \][/tex]
So, the fraction simplifies to:
[tex]\[ 2 \cdot x^{-7} \cdot y^{-4} \][/tex]
Now, let's square the entire simplified expression:
[tex]\[ \left(2 \cdot x^{-7} \cdot y^{-4}\right)^2 \][/tex]
### Squaring each part separately:
#### For the coefficient 2:
[tex]\[ (2)^2 = 4 \][/tex]
#### For the base x:
[tex]\[ (x^{-7})^2 = x^{-7 \cdot 2} = x^{-14} \][/tex]
#### For the base y:
[tex]\[ (y^{-4})^2 = y^{-4 \cdot 2} = y^{-8} \][/tex]
Combining these results, we get:
[tex]\[ 4 \cdot x^{-14} \cdot y^{-8} = \frac{4}{x^{14} \cdot y^8} \][/tex]
Thus, the simplified form of the given expression is:
[tex]\[ \boxed{\frac{4}{x^{14} y^8}} \][/tex]
Your visit means a lot to us. Don't hesitate to return for more reliable answers to any questions you may have. Thanks for stopping by. We strive to provide the best answers for all your questions. See you again soon. We're glad you visited Westonci.ca. Return anytime for updated answers from our knowledgeable team.